COX5A Plays a Vital Role in Memory Impairment Associated With Brain Aging via the BDNF/ERK1/2 Signaling Pathway - Xiyang, Yan-Bin; Liu, Ruan; Wang, Xu-Yang; Li, Shan; Zhao, Ya; Lu, Bing-Tuan; Xiao, Zhi-Cheng; Zhang, Lian-Feng; Wang, Ting-Hua; Zhang, Jie (Frontiers in Aging Neuroscience, 2020)
Cytochrome c oxidase subunit Va (COX5A) is involved in maintaining normal mitochondrial function. However, little is known on the role of COX5A in the development and progress of Alzheimer’s disease (AD). In this study, we established and characterized the genomic profiles of genes expressed in the hippocampus of Senescence-Accelerated Mouse-prone 8 (SAMP8) mice, and revealed differential expression of COX5A among 12-month-aged SAMP8 mice and 2-month-aged SAMP8 mice. Newly established transgenic mice with systemic COX5A overexpression (51% increase) resulted in improvement of spatial recognition memory, recovery of hippocampal CA1 dendrites, and activation of the BDNF/ERK1/2 signaling pathway. Moreover, mice with both COX5A overexpression and BDNF knockdown showed a poor recovery in spatial recognition memory as well as a decrease in spine density and branching of dendrites in CA1, when compared to mice that only overexpressed COX5A. Moreover, in vitro studies supported that COX5A affected neuronal growth via BDNF. In summary, this study was the first to show that COX5A in the hippocampus plays a vital role in ageing-related cognitive deterioration via BDNF/ERK1/2 regulation, and suggested that COX5A may be a potential target for anti-senescence drugs.